Answer:
x:y:z = 12:3:2
Step-by-step explanation:
x = 4y
2y = 3z ⇒ 4y = 6z
⇒ x = 4y = 6z
To find x:
Multiply the coefficients of y & z: 4 × 6 = 24
To find y:
Multiply the coefficients of x & z: 1 × 6 = 6
To find z:
Multiply the coefficients of x & y: 1 × 4 = 4
⇒ x:y:z = 24:6:4 = 12:3:2
Answer:
-1/2 is the work
Step-by-step explanation:
hope this helped
Answer:
Step-by-step explanation:
A(7,1), B(5,-6)
(AB)² = (-6-1)² + (5-7)² = 53
AB = √53
Step-by-step explanation:
I'm trying to solve this problem but there's something wrong
What's the radius of one ball?